Protestant Reformation and Albanian Nationalism - Ylli H. Doci (European Scientific Journal, ESJ, 2017)
The relationship of the Protestant Reformation with Nationalism is understandable if one can appreciate the nature of the general emancipation from the authority as understood during the Middle Ages to the subjectively defined authority that the Reformation brought forth. The connection of the emancipating influence of the Reformation with the Albanian National Awakening is made more clear if one understands not only the thought patterns typically associated with the Reformation, but also some historical dimensions of the Albanian language and education. Therefore, we propose here the thesis that the influence of the Protestant Reformation is discernable also in the history of Albanian Nationalism.